Alanine response to low energy synchrotron x-ray radiation. (15th March 2023) - van den Elzen, P; Sander, T; Palmans, H; McManus, M; Woodall, N; Lee, N; Fox, O J L; Jones, R M; Angal-Kalinin, D; Subiel, A
Abstract: Objective . The radiation response of alanine is very well characterized in the MV photon energy range where it can be used to determine the dose delivered with an accuracy better than 1%, making it suitable as a secondary standard detector in cancer radiation therapy. This is not the case in the very low energy keV x-ray range where the alanine response is affected by large uncertainties and is strongly dependent on the x-ray beam energy. This motivated the study undertaken here. Approach . Alanine pellets with a nominal thickness of 0.5 mm and diameter of 5 mm were irradiated with monoenergetic x-rays at the Diamond Light Source synchrotron, to quantify their response in the 8–20 keV range relative to 60 Co radiation. The absorbed dose to graphite was measured with a small portable graphite calorimeter, and the DOSRZnrc code in the EGSnrc Monte Carlo package was used to calculate conversion factors between the measured dose to graphite and the absorbed dose to water delivered to the alanine pellets. GafChromic EBT3 films were used to measure the beam profile for modelling in the MC simulations. Main results . The relative responses measured in this energy range were found to range from 0.616 to 0.643, with a combined relative expanded uncertainty of 3.4%–3.5% ( k = 2), where the majority of the uncertainty originated from the uncertainty in the alanine readout, due to the small size of the pellets used. Significance . The measured values were in good agreement with previously published data in the overlapping region of x-ray energies, while this work extended the dataset to lower energies. By measuring the response to monoenergetic x-rays, the response to a more complex broad-spectrum x-ray source can be inferred if the spectrum is known, meaning that this work supports the establishment of alanine as a secondary standard dosimeter for low-energy x-ray sources.